The Influence of Hedonism Style, Spiritual Intelligence and Financial Literacy on Student Personal Finance Management (Case study on students of the Faculty of Economics, Indonesian Christian University Toraja) - Stefani Marina Palimbong; Leni Agnes; Elisabet Pali (Proceeding of The International Conference on Economics and Business, 2022)
This research aims to examine the influence of hedonistic style, spiritual intelligence, and financial literacy on students' personal financial management at the Faculty of Economics, Indonesian Christian University, Toraja. This research utilizes quantitative methodologies. There are 1,845 students enrolled in the Faculty of Economics at the Indonesian Christian University Toraja. The Slovin formula was applied to 95 individuals as research samples. Primary data and secondary data are the types of data that are used, and the SPSS version 25 program is used to manage them. Questionnaires utilizing the probability sampling approach, proportionate stratified random sampling, are among the data collecting methods. This research employs instrument test, classical assumption test, multiple linear regression analysis, and hypothesis testing as data analysis approaches. At a significance level of 5%, the results of the study indicated that financial literacy did not have a significant positive influence on the personal financial management of students, whereas the hedonistic style variable had a positive but non-significant effect. Spiritual intelligence has a beneficial and significant impact on the financial management of pupils. Styles of hedonism, spiritual intelligence, and financial literacy all have positive and significant effects on personal financial management, as evidenced by the estimated F value of 32.210, which is more than the F table value of 2.705 and has a significance level of 0.000 less than 0.05.